2014
DOI: 10.1111/ggi.12192
|View full text |Cite
|
Sign up to set email alerts
|

Olive leaf extract decreases age-induced oxidative stress in major organs of aged rats

Abstract: The present results suggest that OLE seems to be useful for decreasing oxidative stress in examined tissues by acting as an anti-oxidant itself without affecting the anti-oxidant system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Under the present experimental conditions, our data demonstrate that (i) polyphenols can partially protect from ethanol-induced oxidative stress although further studies analyzing multiple methods of oxidative stress are required; (ii) polyphenols by themselves do not appear to potentiate the natural endogenous antioxidant resources following chronic alcohol exposure; (iii) however, polyphenols administration by themselves may potentiate the natural endogenous antioxidant resources in normal conditions. Similar findings were previously observed in aged rats treated with an olive leaf extract [16] showing a decrease in oxidative stress by acting as an antioxidant per se but not affecting the antioxidant system. In this study, we administered a blend of polyphenols containing mostly hydroxytyrosol.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Under the present experimental conditions, our data demonstrate that (i) polyphenols can partially protect from ethanol-induced oxidative stress although further studies analyzing multiple methods of oxidative stress are required; (ii) polyphenols by themselves do not appear to potentiate the natural endogenous antioxidant resources following chronic alcohol exposure; (iii) however, polyphenols administration by themselves may potentiate the natural endogenous antioxidant resources in normal conditions. Similar findings were previously observed in aged rats treated with an olive leaf extract [16] showing a decrease in oxidative stress by acting as an antioxidant per se but not affecting the antioxidant system. In this study, we administered a blend of polyphenols containing mostly hydroxytyrosol.…”
Section: Discussionsupporting
confidence: 90%
“…We found that FORT levels in blood serum were significantly higher in EtOH mice as compared to controls. Quite interestingly, the presence of polyphenols seems to have partially counteracted this effect (F [3,16] ¼ 299.95, P < 0.01 in the ANOVA: see Fig. 1A for post-hoc comparisons).…”
Section: Oxidative Stress Evaluationmentioning
confidence: 95%
“…Interestingly, OLE and the main component HT proved to have antioxidant effects [ 43 , 44 , 45 ]. OLE treatment has improved the hepatic GSH level in aged rats [ 46 ]. In our report, OLE treatment ameliorated acrolein-exaggerating myoardial injury may partly result from OLE restoring the level of GSH that bound acrolein, which attenuated ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several investigators have found that AGE levels were increased in the serum and tissues of aged animals, and humans erythrocytes and several tissues, such as the liver, heart and brain, have been observed in experimental animals. Increases in oxidative stress parameters have also been detected in humans with aging …”
Section: Introductionmentioning
confidence: 99%